A sleep guide for the mature adult - Walsleben, Joyce A., 1939- (Cambridge Scholars Publishing, 2019)
Having trouble getting your dreamed-of sleep after you retired? No longer able to stay awake after 8PM? Now that you have time on your hands, why can't you sleep at night? This book provides answers to these questions and more, offering necessary information and advice. As we change with age, sleep also changes. Why not encourage it to change for the better? The book explains how, from recognizing telling symptoms to just organizing a different schedule.